Altered intrinsic activity and functional connectivity in two animal models with opposing fear memories. Issue 8 (23rd May 2018) - Yang, Jianjun; Pan, Wei; Ji, Muhuo
Abstract : Post-traumatic stress disorder and sepsis-associated encephalopathy are two common neuropsychiatric disorders, but to some extent with opposing cognitive performance. However, the neural mechanisms underlying these two different phenomena remain poorly understood. In our study, the amplitude of low-frequency fluctuations (ALFF) of spontaneous blood oxygen level-dependent signals was used to assess regional disturbances in two animal models with opposing cognitive performance, namely post-traumatic stress disorder and sepsis-associated encephalopathy. Then, we examined whether the memory-relevant brain regions with impaired ALFF altered functional connectivity within the whole brain. Here, we showed that lipopolysaccharide challenge and footshock induced significantly different cognitive performance. We found significant group differences in ALFF in the bilateral dentate gyrus. In addition, our study showed that footshocks induced a significant decrease in functional connectivity between the left dentate gyrus and the visual cortex compared with the lipopolysaccharide group. Notably, cognitive performance was associated with ALFF values in the right dentate gyrus. In conclusion, our data suggested that damaged regional spontaneous activity and abnormal functional connectivity might be differently involved in two opposing fear memories. Abstract : Supplemental Digital Content is available in the text.